Web sonification with synesthesia tools - Piassi Passos Bodo, Roberto; Luiz Schiavoni, Flávio (Música Hodie, 2018)
In this paper, we present an investigation on sonification of web pages involving three media: HTML struc- ture, page text and images. In our approach, HTML pages are read as musical scores; text elements are also read as musical scores following the idea present in notation systems like ABC; and images are read as wave files. We deve- loped a set of tools for website sonification which can be used to explore musical creativity and to create new soun- ds based on the web pages content. In addition, we show how to create sounds and visual feedback using this tool.